Rural Crafts: A study in South Wiltshire. Issue 1 (1st March 2021) - Cook, Hadrian; Stearne, Kathy
Rural Crafts are crafts with agrarian roots, but they are not easily located historically, or within today's developed markets. This study stresses Rural over Heritage Crafts (based in manual skills and traditional materials, designs and techniques), although the two are not mutually exclusive. Rural Crafts are considered, present and past, through interviews with practitioners based in South Wiltshire. The study embraces networks of crafters, interviews with individuals and a focus for a rural craft event located at the Harnham Water Meadows at Salisbury, a historic location. It is established that, while few participants sustained themselves financially through their craft, it was clear that participation is 'value driven', providing personal benefits. The ethos of sustainability is a strong theme, both in sourcing materials and in the processes employed, especially true for individuals working with wood and thatching. Few clear similarities are found from past cottage industries, although the sense of continuity in craft is still strong. Networks included craft associations, and opportunities for informal learning, but there is a lack of formal training opportunities. This finding may be historic, as most people interviewed were over 60 years. As well as an age bias, there is a strong gender bias with men dominating regular part-time or full-time paid occupations and women treating their craft more as a hobby. Most people treat sales of any products as a bonus, and the future of such activities is dependent more upon personal interests and networks than on formally trained (often younger) individuals, more so than formal training delivered through individual organizations or companies. Otherwise, our conclusions are in line with modern ideas of personal, well-being and social benefits derived from craft activities.